Induction of antigen specific intrahepatic CD8+ T cell responses by a secreted heat shock protein based gp96-Ig-PfCA malaria vaccine - Padula, Laura; Fisher, Eva; Wijayalath, Wathsala; Patterson, Noelle B.; Huang, Jun; Ganeshan, Harini; Robinson, Tanisha; Bates, François A.; Hanson, Margaret A.; Martin, Monica L.; Rivas, Katelyn; Garcia, Denisse; et al. (Frontiers in Immunology, 2023)
Introduction A highly efficacious and durable vaccine against malaria is an essential tool for global malaria eradication. One of the promising strategies to develop such a vaccine is to induce robust CD8+ T cell mediated immunity against malaria liver-stage parasites. Methods Here we describe a novel malaria vaccine platform based on a secreted form of the heat shock protein, gp96-immunoglobulin, (gp96-Ig) to induce malaria antigen specific, memory CD8+ T cells. Gp96-Ig acts as an adjuvant to activate antigen presenting cells (APCs) and chaperone peptides/antigens to APCs for cross presentation to CD8+ T cells. Results Our study shows that vaccination of mice and rhesus monkeys with HEK-293 cells transfected with gp96-Ig and two well-known Plasmodium falciparum CSP and AMA1 (PfCA) vaccine candidate antigens, induces liver-infiltrating, antigen specific, memory CD8+ T cell responses. The majority of the intrahepatic CSP and AMA1 specific CD8+ T cells expressed CD69 and CXCR3, the hallmark of tissue resident memory T cells (Trm). Also, we found intrahepatic, antigen-specific memory CD8+ T cells secreting IL-2, which is relevant for maintenance of effective memory responses in the liver. Discussion Our novel gp96-Ig malaria vaccine strategy represents a unique approach to induce liver-homing, antigen-specific CD8+ T cells critical for Plasmodium liver-stage protection.